Home > Calculus calculators > Trigonometry calculator

Trigonometry

Method

 1. Simplifying trigonometric equations, proving identities Expression sin^2(30)*cos^2(60)sin(30)*cos(60)+sin(30)*cos(60)sin(30)*csc(30)-sin(60)*csc(60)2sin^2(30)*3cos^2(60)(2tan(60))/(1+tan^2(60))(3sec(60)+2tan(45)+csc(30))/(sin^2(60)+cot^2(45))(3sec(60)+2tan(45)+csc(30))(sin^2(60)+cot^2(45))sin(30)*cos(45)*tan(60)=sin(45)*cos(60)*cot(30)tan(45)*sec(72)*sin(58)=cos(32)*csc(18)sin^2(34)-cot^2(46)-cos^2(56)+tan^2(44)=sec^2(62)-csc^2(28)sin(30)*cos(45)*tan(60)=sin(45)*cos(60)*cot(30)tan(45)*sec(72)*sin(58)=cos(32)*csc(18)sin^2(34)-cot^2(46)-cos^2(56)+tan^2(44)=sec^2(62)-csc^2(28)sin^2(50)+sin^2(40)=1sin(35)*sec(55)-cos(55)*csc(35)=tan(25)-cot(65)2sin(30)+2tan(45)-3cos(60)-2cos^2(30)=02sec^2(x)-2sin(x)sec(x)sin(x)cot(x)cot(x)sin(x)tan(x)+cot(x)cos(x)+cot(x)tan(x)sin(x)+cos(x)cot^4(x)+cot^2(x)cos^2(x)csc^2(x)-cos^2(x)tan^2(x)-sin^2(x)(csc(x)-sin(x))(sec(x)-cos(x))(tan(x)+cot(x))(sec(x)-cos(x))(csc(x)-sin(x))1+1/tan^2(x)csc(x)/cos(x)-cos(x)/sin(x)sec(x)/2(tan(x)+cot(x))sec(x)/(2(tan(x)+cot(x)))(tan^2(x)-cot^2(x))/(sin^2(x)-cos^2(x))(tan^2(x)+cot^2(x))/(tan^2(x)-cot^2(x))(tan^2(x)-cot^2(x))/(tan^2(x)+cot^2(x))(3sin(x)+5cos(x))^2+(3cos(x)-5sin(x))^2(1+cos(x))/sin(x)+sin(x)/(1+cos(x))sin^2(x)cos(x)+sin^3(x)+cos^2(x)sin(x)+cos^3(x)(sin^4(x)-cos^4(x))/(sin^2(x)-cos^2(x))5cos^2(x)+2sin^2(x)2cos^2(x)+sin^2(x)(sin^4(x)+cos^4(x))
2. Find the value of all the other five trigonometric functions or solve expression
If = then

 1. Find the value of all the other five trigonometric functions sin(x)cos(x)tan(x)csc(x)sec(x)cot(x) 2. Solve expression If sin(x)=5/13 then find other trigonometry If cos(x)=12/13 then find other trigonometry If tan(x)=5/12 then find other trigonometry If csc(x)=13/5 then find other trigonometry If sec(x)=13/12 then find other trigonometry If cot(x)=12/5 then find other trigonometry If sin(x)=3/5 then solve cos(x)csc(x)+tan(x)sec(x)If tan(x)=1/2 then solve (1-tan^2(x))/(1+tan^2(x))+(2tan(x))/(1+tan^2(x))If sin(x)=4/5 then solve (1-sin(x))/cos(x)+cos(x)/(1-sin(x))If cos(x)=3/5 then solve (1-sin(x))/cos(x)+cos(x)/(1-sin(x))

SolutionHelpExample-1Example-2Input functions